2004
DOI: 10.1007/s00455-003-0504-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Normal Deglutition with the Help of Rectified Surface Electromyography Records

Abstract: Surface electromyographic (sEMG) studies were performed on 300 normal adults to estimate normal values of sEMG records of muscle activity in the detection and evaluation of stages of normal swallowing. Our study was a prospective observational study of healthy volunteers. The parameters evaluated during swallowing include the timing, amplitude (voltage), and graphic patterns of activity of the orbicularis oris, masseter, submental, and laryngeal strap muscles covered by the platysma. Three tests were examined:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
3
7

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 12 publications
2
62
3
7
Order By: Relevance
“…Therefore, it is an additional tool for the establishment and location -oral, pharyngeal, and esophageal -of the causes for dysphagia and odynophagia (14) . Participants were instructed as follows: "place the capsule on your tongue, together with the customary amount of food you use when taking any medication.…”
Section: Videofluoroscopic Swallowing Studymentioning
confidence: 99%
“…Therefore, it is an additional tool for the establishment and location -oral, pharyngeal, and esophageal -of the causes for dysphagia and odynophagia (14) . Participants were instructed as follows: "place the capsule on your tongue, together with the customary amount of food you use when taking any medication.…”
Section: Videofluoroscopic Swallowing Studymentioning
confidence: 99%
“…Surface electromyography (sEMG) has been reported to provide a non-invasive method of assessing certain aspects of complex muscle activity for deglutition [4]. Miura et al [5] reported that the carbonated or cooled beverages have effect on the submental muscles and these responses can be examined by sEMG.…”
Section: Introductionmentioning
confidence: 99%
“…To address this issue, Neuroscan EEG systems include two bipolar surface EMG electrodes, which can be placed over a particular muscle group to identify muscle activity during movement. The following muscle complexes are known to provide physiological references for analyzing muscular activity during swallowing: the orbicularis oris muscles represent the oral phase; the masseter muscles represent the oral phase; the submental muscle group represent oral and pharyngeal phases (Perlman & Schulze-Delrieu, 1998;Vaiman et al, 2004); the infrahyoid muscle group represent the pharyngeal and esophageal phases (Balata et al, 2012;Ding, Larson, Logemann, & Rademaker, 2002;Ertekin et al, 1997;Spiro & Gay, 2004;Vaiman, Gabriel, Eviatar, Segal, 2005;Vaiman & Eviatar, 2011). While electrophysiological data obtained from the submental muscle group measures muscular activity during both the oral and pharyngeal phases (Ding et al, 2002), the infrahyoid muscle group allows for interpretation of pharyngeal phase activity that is dissociated from the oral phase.…”
Section: Mu Cluster Activity During Different Phases Of Swallowingmentioning
confidence: 99%
“…The electrooculogram (EOG) recorded eye movements using two VEOG electrodes placed superior and inferior to the left eye and two HEOG electrodes placed lateral and medial to the left eye. In an attempt to identify the time course of muscle activity generated during hyolaryngeal excursion, two bipolar surface electromyography (EMG) electrodes were placed over the infrahyoid muscle complex (Logemann, 1998;Perlman, Palmer, McCulluch & Vandaele, 1999;Vaiman, Eviatar & Segal, 2004;Vaiman & Nahlieli, 2009). Additionally, cardiac-related artifacts were recorded using two electrocardiography (ECG) electrodes placed over the right and left common carotid arteries.…”
Section: Eeg and Emg Data Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation